2015
DOI: 10.1007/s10409-015-0435-4
|View full text |Cite
|
Sign up to set email alerts
|

Surface stress effect on the vibration and instability of nanoscale pipes conveying fluid based on a size-dependent Timoshenko beam model

Abstract: Presented in this paper is a precise investigation of the effect of surface stress on the vibration characteristics and instability of fluid-conveying nanoscale pipes. To this end, the nanoscale pipe is modeled as a Timoshenko nanobeam. The equations of motion of the nanoscale pipe are obtained based on Hamilton's principle and the Gurtin-Murdoch continuum elasticity incorporating the surface stress effect. Afterwards, the generalized differential quadrature method is employed to discretize the governing equat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(19 citation statements)
references
References 51 publications
0
19
0
Order By: Relevance
“…By substituting Eqs. (8)(9)(10)(11) into Eq. (1), the strain energy owing to both the variations of the classical and higher order stresses with respect to the initial configuration can be obtained as…”
Section: Derivation Of Governing Equations and Boundary Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…By substituting Eqs. (8)(9)(10)(11) into Eq. (1), the strain energy owing to both the variations of the classical and higher order stresses with respect to the initial configuration can be obtained as…”
Section: Derivation Of Governing Equations and Boundary Conditionsmentioning
confidence: 99%
“…Some experiments have demonstrably approved the size-dependent mechanical behaviors in microbeams [4][5][6][7] and have shown that size-dependency is an inherent property that gets important when the thickness of A C C E P T E D M A N U S C R I P T 3 beam is comparable to the internal material length scale parameter. Therefore, a variety of examinations have been performed on the estimation of mechanical characteristics of small-scale structures based upon the non-classical continuum mechanics theories [8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Reza and Shahrokh [40] investigated the impacts of surface density on the nonlinear vibration of Timoshenko and Euler-Bernoulli nanobeams. Ansari et al [41] carried out an investigation of the surface effect on the vibration characteristics and instability of fluid-conveying nanoscale pipes. They summarised that surface modulus and surface residual stress have great impacts on the frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…Employing the micropolar theory, Ansari et al 6 reported the free vibration behavior of microscale beams and plates considering a three dimensional formulation. Based on Timoshenko beam theory (TBT) and Gurtin-Murdoch continuum elasticity, Ansari et al 7 presented the vibration and instability characteristics of fluid-conveying nanoscale pipes. Based on HSDT and non-linear finite element method (FEM), non-linear free vibration behavior of laminated composite shells were investigated under uniform thermal loading 8,9 and also considering hygrothermal environment.…”
Section: Introductionmentioning
confidence: 99%